Respuesta :
Answer:
x = 2
y = 0
Step-by-step explanation:
We can solve using substitution, substitute y in the first equation with the second equation:
-(-6x + 12) + 3x = 6
Distribute the negative sign:
6x - 12 + 3x = 6
Combine like terms:
9x - 12 = 6
Isolate the variable and solve for x by adding 12 in both sides:
9x = 18
x = 2
Substitute 2 with x in any equation to find the value of y:
-y + 3(2) = 6
-y + 6 = 6
Subtract 6 in both sides to isolate the variable:
-y = 0
0/-1 = 0
y = 0
Our answer would be x = 2 and y = 0
Answer:
(2,0)
Step-by-step explanation:
I'm going to use substitution since one of the variables in one of the equation is already solved for.
-y+3x=6
y=-6x+12
I'm going to replace the first y with the second y which is (-6x+12).
This gives me:
-(-6x+12)+3x=6
Distribute:
6x-12+3x=6
Combine like terms:
9x-12=6
Add 12 on both sides:
9x=18
Divide both sides by 9:
x=2
If x=2 and y=-6x+12, then y=-6(2)+12=-12+12=0.
The solution (the intersection) is (2,0).